Peculiarities of implementing governance in the system of social security - Kryshtanovych, Myroslav; Petrovskyi, Petro; Khomyshyn, Iryna; Bezena, Ivan; Serdechna, Iryna (Business, Management and Economics Engineering, 2020)
Purpose – the primary purpose of the study is to identify the main threats to the process of ensuring social security and finding ways to establish a connection between economic and social security. Research methodology – the methodological basis is a system of complementary philosophical, general scientific and unique methods of cognition of socio-political phenomena, in particular systemic-structural, comparatively retrospective, institutional and structural-functional, diagnostics and forecasting, general methods of analysis and synthesis, etc. Findings – our results made it possible to establish which particular threats most affect the social security of the countries of Eastern Europe and the calculation results will help establish the country needs a connection between economic and social security. Research limitations – we did not take into account a significant number of indicators characterising the state of social security of the state. The threats we have highlighted are compassionate. In the future, it is necessary to pay considerable attention to the process of assessing the level of social security of the state in order to determine whether it is necessary to state which government measures or not. Practical implications – сertain threats and models can be used by countries of Eastern Europe to form the necessary measures to counter them; Originality/Value – the study covers one of the least explored areas, namely social security, which has not been explored for a long time in the context of identifying threats. Social Security Model IDEF0 Formed.